Study of Force Feedback in Steer-By-Wire Vehicles for Driving Simulator - Abdul Wali, Muhamad Ammar (IRC, 2016)
In Steer-by-wire(SBW) system, drivers use the sense of steering feel to acquire information about the road that helps them in driving tasks. Steer-by-wire(SBW) system removes the mechanical linkages between handwheel and front wheels where it enhances controllability of vehicle dynamic characteristic and safety of car crash. Preliminary research showed that due to the mechanical decoupling of the handwheel and front wheels, they do not have any inherent steering feel and, as a result, drivers lose this important source of communication - driving feedback. In the present research, the technique of creating an artificial steering feel in these SBW vehicles allows the driver to sense the force/haptic feedback. The approach taken was to develop a model with sets of mathematical equations to generate force feedback using MATLAB/SIMULINK block diagram and display a simple driving simulator using 3D animation software inside MATLAB. Techniques of simulation modelling and data were obtained from various sources discussed further inside the literature review to understand and study the characteristic of Force Feedback model generated inside different manoeuvre of the car.